2015
DOI: 10.3390/buildings5030880
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Agile Workspace and Remote Working on Experiences of Privacy, Crowding and Satisfaction

Abstract: Occupant density is an important and basic metric of space use efficiency. It affects user experience of privacy, crowding and satisfaction. The effect of agile working has been two fold. Firstly, offices have an increasing range of workspace settings such as break out space, collaborative space and contemplative space in contrast to the traditional workspace settings of assigned desks and formal meeting rooms. Secondly, office workers have become increasingly mobile as they are able to work from a greater var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…Fast change occurred as internet and cell-phones first became widespread in the 1990s and early 2000s: the period following the introduction of smart phones (introduced in 2007) witnessed slower change in Canadian cities. As some of the challenges of workplace mobility – such as coordination, team work, quality of communication, concentration, privacy, confidentiality, loneliness, over-stimulation – become evident (Felstead and Henseke, 2017; Hekkala et al, 2017; Keeling et al, 2015; Pochepan, 2018) its growth may further slow. Workplace mobility will not disappear and probably will not decrease: rather, it may plateau as organisations and workers take stock of new workplace possibilities and determine whether they are suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Fast change occurred as internet and cell-phones first became widespread in the 1990s and early 2000s: the period following the introduction of smart phones (introduced in 2007) witnessed slower change in Canadian cities. As some of the challenges of workplace mobility – such as coordination, team work, quality of communication, concentration, privacy, confidentiality, loneliness, over-stimulation – become evident (Felstead and Henseke, 2017; Hekkala et al, 2017; Keeling et al, 2015; Pochepan, 2018) its growth may further slow. Workplace mobility will not disappear and probably will not decrease: rather, it may plateau as organisations and workers take stock of new workplace possibilities and determine whether they are suitable.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, and irrespective of the inconsistent research findings on OPO efficacy, contemporary organisations continue to accommodate their employees in a range of different OPO configurations. These include activity-based workspaces (ABW – where employees choose their workstation according to the work activity carried out at any one time; Keeling et al, 2015 see also Engelen et al, 2019) and agile workspaces (AW – that is, constantly transforming, adjusting and responding to organisational learning, see Joroff et al, 2003; Keeling et al, 2015). For example, Telstra 1 recently moved their employees into an ABW workspace in their Brisbane office.…”
Section: What We Know About Physical Environment Of Office Work: Amentioning
confidence: 99%
“…In addition to the traditional and open plan types of offices, in the literature it is possible to find another term called agile workspaces or agile offices that have characteristics related to traditional and open plan types of office, but presents an another kind of work approach composed of a great variety of work configurations, such as: shared desks, informal spaces, relaxation rooms and contemplative spaces, so occupants can do their activities without a previously defined space [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keeling et al [6] in their study compared agile workspaces with traditional types of office design such as open spaces and private environments to investigate the effects on privacy, crowding and satisfaction at work. The result has shown that agile workspaces is a distinct typology from open plan typologies and cellular offices.…”
Section: Literature Reviewmentioning
confidence: 99%